Effects of the harvesting technique and external stenting on progression of vein graft disease 2 years after coronary artery bypass. (21st March 2022) - Sandner, Sigrid E; Donovan, Terrence John; Edelstein, Stav; Puskas, John D; Angleitner, Philipp; Krasopoulos, George; Channon, Keith; Gehrig, Thomas; Rajakaruna, Cha; Ladyshenskij, Leonid; De Silva, Ravi; Bonaros, Nikolaos; et al.
Abstract: OBJECTIVES: In a post hoc analysis of the VEST III trial, we investigated the effect of the harvesting technique on saphenous vein graft (SVG) patency and disease progression after coronary artery bypass grafting. METHODS: Angiographic outcomes were assessed in 183 patients undergoing open (126 patients, 252 SVG) or endoscopic harvesting (57 patients, 114 SVG). Overall SVG patency was assessed by computed tomography angiography at 6 months and by coronary angiography at 2 years. Fitzgibbon patency (FP I, II and III) and intimal hyperplasia (IH) in a patient subset were assessed by coronary angiography and intravascular ultrasound, respectively, at 2 years. RESULTS: Baseline characteristics were similar between patients who underwent open and those who underwent endoscopic harvesting. Open compared with endoscopic harvesting was associated with higher overall SVG patency rates at 6 months (92.9% vs 80.4%, P = 0.04) and 2 years (90.8% vs 73.9%, P = 0.01), improved FP I, II and III rates (65.2% vs 49.2%; 25.3% vs 45.9%, and 9.5% vs 4.9%, respectively; odds ratio 2.81, P = 0.09) and reduced IH area (-31.8%; P = 0.04) and thickness (-28.9%; P = 0.04). External stenting was associated with improved FP I, II and III rates (odds ratio 2.84, P = 0.01), reduced IH area (-19.5%; P < 0.001) and thickness (-25.0%; P < 0.001) in the open-harvest group and reduced IH area (-12.7%; P = 0.01) and thickness (-9.5%; P = 0.21) in the endoscopic-harvest group. CONCLUSIONS: A post-hoc analysis of the VEST III trial showed that open harvesting is associated with improved overall SVG patency and reduced IH. External stenting reduces SVG disease progression, particularly with open harvesting. Abstract : Saphenous vein grafts (SVG) remain the most commonly used conduit in coronary artery bypass grafting (CABG).